Dibujar conceptos jurídicos : una experiencia docente alternativa - Legarre, Santiago (2015)
"This paper is based on a paper presented at the International Association of Law Schools (IALS) meeting, held in Mysore, India, March 6?8, 2013." -- This article suggests a new way of teaching legal concepts: the use of drawings by the students. In order to promote creativity the instructor uses a system of contests and prizes. This model of teaching especially caters for visual students. A main conclusion of this article is that law can be adequately understood and studied through visual tools.